Non-invasive Evaluation of Brain Death Caused by Traumatic Brain Injury by Ultrasound Imaging - Niu, Ningning; Tang, Ying; Hao, Xiaoye; Wang, Jing (Frontiers in Neuroinformatics, 2020)
Objectives: To investigate the clinical value of noninvasive ultrasound imaging in the evaluation of brain death caused by traumatic brain injury. Methods: 34 patients with acute severe traumatic brain injury were admitted to hospital within 48 hours after injury. All patients were monitored intracranial pressure, transcranial Doppler, echocardiography examination, collection intracranial pressure, MCA-Vs, MCA-Vd, MCA-Vm, EF, LVMPI, RVMPI and other indicators, and combined with clinical conditions and other related data for comparative study and statistical analysis. Results: The blood flow spectrum was characterized by diastolic retrograde blood flow spectrum pattern and nail waveform spectrum shape when the patient had clinical brain death. For the parameters of transcranial Doppler, there were significant differences in MCA-Vm and PI between clinical brain death group and normal control group (P < 0.05). For the parameters of echocardiography, there were statistically significant differences in EF, LVMPI and RVMPI between clinical brain death group and normal control group (P < 0.05). Conclusions: Noninvasive dynamic monitoring of cerebral hemodynamics and cardiac function parameters in patients with severe craniocerebral injury can provide a high accuracy and reliability for the preliminary diagnosis of brain death in patients with severe craniocerebral injury. It is helpful for early evaluation of prognosis and provides effective monitoring methods and guidance for clinical treatment.